Potential of Ambient Media Use as Advertising Media in the Future - Mohamed Taffarul Rizky; Hendri Prasetya; Mustiawan Mustiawan (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Ambient media is proven to be more effective in attracting attention and increasing audience recall than conventional advertising so that it overcomes the challenge of ad fatigue in digital advertising. Based on these findings, ambient media has great potential as a more interactive, memorable and unobtrusive marketing strategy which makes it an innovative solution in the face of future advertising industry dynamics. Therefore, advertisers are expected to optimize the creative and experiential elements in the implementation of ambient media in order to enhance the appeal and effectiveness of their campaigns. The aim of this study is to explore the potential of ambient media as an innovative and effective advertising medium in the future. Using the Systematic Literature Review (SLR) method, this research analyzed various studies which discussed ambient media in marketing communication strategies. The results show that ambient media has the advantage of creating creative messages which rely on visual surprise, audience interaction, and integration with the environment, while being able to build emotional engagement through an Experiential Marketing approach that focuses on sensory, emotional, and social experiences.